Pengaruh Motivasi Orang Tua Terhadap Minat Belajar Pada Mata Pelajaran Pendidikan Agama Kristen Siswa Kelas XI SMA Swasta PGRI 20 Siborongborong Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 (Jurnal Pendidikan Agama dan Teologi, 2023)
The purpose of this study was to determine the effect of parental motivation on interest in learning Christian Religious Education Class XI Students of PGRI 20 Private High School Siborongborong, North Tapanuli Regency, 2023/2024 Academic Year. The research method used is a quantitative method with inferential descriptive data analysis. The population is all students of class XI SMA PGRI 20 Siborongborong in the 2023/2024 academic year who are Protestant Christians as many as 245 people and a sample of 58 people is determined using the Proportionate Stratified Random Sampling technique (random sample). Data were collected using a positive closed questionnaire of 45 items, namely 20 items for variable X and 25 items for variable Y. The results of data analysis showed that there was an influence of parental motivation on interest in learning in the subject of Christian Religious Education for class XI students at the private high school PGRI 20 Siborongborong North Tapanuli Regency 2023/2024 Academic Year: 1) Test requirements analysis: a) a positive relationship test obtained rxy = 0.558 > rtable(a=0.05, n=58) = 0.254. b) Testing a significant relationship obtained a value of tcount= 5.034 > ttable(a=0.05, dk=n-2=58)= 2.000. 2) Influence test: a) Regression equation test, obtained regression equation Y=41.87+0.52X. b) Regression coefficient of determination test (r2) = 31.2%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=28, dk denominator=n-2=58-2=56) namely 25.32 > 1.39. Thus Ha is accepted and H0 is rejected.